2013
DOI: 10.1159/000354901
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypoxia, High Glucose, and Low Serum on the Growth Kinetics of Mesenchymal Stem Cells from Deciduous and Permanent Teeth

Abstract: The therapeutic potential of mesenchymal stromal cells depends on their ability to survive and proliferate under adverse in vivo scenarios in a particular disease. In most of the sites of injury, especially in diabetic wounds, there can be hypoxia, hyperglycemia, and ischemia, leading to a lack of nutrients. Hence, the aim of our present study was to investigate the influence of hypoxia, high glucose, and low serum concentrations on the growth kinetics and proliferative potential of human dental pulp stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
(29 reference statements)
2
34
0
Order By: Relevance
“…The consequences of anoxic stress towards the dental stem cells (hDFSCs) were analyzed. As previously shown by Kanafi and colleagues migration and proliferation of human dental pulp stem cells (SHEDs and DPSCs) were increased under hypoxic conditions of 2.3% O 2 und 5% CO 2 compared to normoxic conditions33. Even 3% of oxygen stimulated migration of mesenchymal bone marrow stem cells133435.…”
Section: Discussionmentioning
confidence: 68%
“…The consequences of anoxic stress towards the dental stem cells (hDFSCs) were analyzed. As previously shown by Kanafi and colleagues migration and proliferation of human dental pulp stem cells (SHEDs and DPSCs) were increased under hypoxic conditions of 2.3% O 2 und 5% CO 2 compared to normoxic conditions33. Even 3% of oxygen stimulated migration of mesenchymal bone marrow stem cells133435.…”
Section: Discussionmentioning
confidence: 68%
“…SHED also modulate immune responses of interleukin-17-producing helper T (Th17) cells, regulatory T cells (Tregs), and dendritic cells [ 16 , 17 ]. Recent studies have evaluated the latent potential of SHED in tissue engineering for bone regeneration [ 18 , 19 ] and cell-based therapy for a variety of refractory systemic diseases, including systemic lupus erythematous, spinal cord injury, Parkinson’s disease, and diabetes [ 16 , 20 22 ]. Furthermore, cryopreservation of dental pulp tissues from human deciduous teeth has succeeded [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases of tissue injury, there can be hypoxia and ischemia, leading to a lack of nutrients. Therefore, it is important for BM‐MSCs to endure and survive in low‐nutrition microenvironment . Our study indicated that in low‐serum cultural medium, BM‐MSCs exhibited obviously arrested activity and high apoptosis rate.…”
Section: Discussionmentioning
confidence: 71%